Productive efficiency of Premier League teams using an enhanced data envelopment analysis approach - Jan Šíma; Josef Voráček; Jiří Kraft; Veronika Krause (Karolinum Press, 2023)
The study focuses on evaluating the economic efficiency of professional football clubs. It builds on the Haas Study, which examines the effectiveness of individual clubs through Data Envelopment Analysis (DEA). DEA analyses different types of inputs and outputs for homogeneous production units (in this case football clubs). The thesis proposes the modification of this model. The author considers the initial "hometown population" contribution of Haas as particularly outdated with regard to the increasing commercialisation of professional football and globalisation of the market, where the size of demand is primarily determined by the global popularity measured in terms of interest of the fans, sponsors, and television broadcasting companies. The global popularity of the club can easily be estimated at present using the number of fans in social networks. The clubs reflect this target on the side of the outputs - "increase of the number of fans in the social network". Facebook was chosen as the representative of the social networks. The proposed model is used in the paper for calculation of the economic efficiency of the participants in the English Premier League in the 2016-2017 season.